2016
DOI: 10.1007/s40258-016-0293-7
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Comparison of the EQ-5D-5L, DEMQOL-U and DEMQOL-Proxy-U in a Post-Hospitalisation Population of Frail Older People Living in Residential Aged Care

Abstract: Running head: quality of life of frail older people in residential aged care Results: There was a large divergence in mean (SD) utility scores at baseline for the EQ-5D-5Land DEMQOL-U [EQ-5D-5L mean 0.21 (0.19); DEMQOL-U mean 0.79 (0.14)]. However, at 4 weeks a stronger degree of convergence was evident [EQ-5D-5L mean 0.45(0.38); DEMQOL-U mean 0.58 (0.38). The EQ-5D was more responsive to the physical recovery trajectory experienced by frail older people following surgery to repair a fractured hip, whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
(42 reference statements)
1
26
0
Order By: Relevance
“…We also identified a moderate correlation between the informal-carer-completed EQ-5D-5L-proxy and DEMQOL-Proxy-U, with the DEMQOL-Proxy-U providing higher utility scores especially at lower levels. These results closely resemble those of the 2 comparable Australian studies 4,9 (eg, we reported rho = 0.386, versus 0.389 in 1 of the Australian studies, and a mean difference of 0.214 versus 0.202). These results might have arisen because the EQ-5D-5L has a much lower bound than the DEMQOL-Proxy-U (20.285 vs 0.363, respectively).…”
Section: If Researchers Opt For Proxy-completed Pbms Does It Matter supporting
confidence: 87%
See 2 more Smart Citations
“…We also identified a moderate correlation between the informal-carer-completed EQ-5D-5L-proxy and DEMQOL-Proxy-U, with the DEMQOL-Proxy-U providing higher utility scores especially at lower levels. These results closely resemble those of the 2 comparable Australian studies 4,9 (eg, we reported rho = 0.386, versus 0.389 in 1 of the Australian studies, and a mean difference of 0.214 versus 0.202). These results might have arisen because the EQ-5D-5L has a much lower bound than the DEMQOL-Proxy-U (20.285 vs 0.363, respectively).…”
Section: If Researchers Opt For Proxy-completed Pbms Does It Matter supporting
confidence: 87%
“…Three existing (repeated) cross-sectional studies compared various combinations of resident-completed and proxy-completed versions of the EQ-5D and the DEMQOL in Britain 19 or Australia. 4,9 In contrast to our study, these included people without dementia 4 or people who were restricted to unrepresentative subgroups (eg, people recently hospitalized 9 or with significant depressive symptoms). 19 None of these studies compared formal-carer with informal-carer proxies or DEMQOL-Proxy-U with other quality of life measures (QOL-AD-NH and QUALID), and of the studies did not compare self-and proxy-responses for the same residents.…”
Section: Comparison With Existing Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Interventions aimed at alleviating symptoms which may lead to agitation in advanced dementia, such as treatment of pain according to the stepwise protocols can be effective (Husebo et al, 2011). Economic evaluation of such interventions should use a standard outcome of quality-adjusted life years, using measures such as DEMQOL (Ratcliffe et al, 2017) in a clinical trial, to allow for costeffectivenessanalysis.…”
Section: Directions For Further Researchmentioning
confidence: 99%
“…MMSE; EQ5D and DEMQoL (33)(34)(35)(36), are used in almost all RCTs conducted in care homes. Additionally, clinical indicators such as hospitalisations, falls, and death rates are routinely reported (see Appendix 2: Examples of data available from each trial.…”
Section: Database Of Trial Summariesmentioning
confidence: 99%